Khalayak dalam Komunikasi Politik: Peran dan Pengaruhnya dalam Keberhasilan Proses Komunikasi - Sirait, Mhd Fauziah; Siregar, Sarifah Aini; fika, Nurfatin Sya (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2024)
Khalayak is commonly referred to as the recipient, the target, the reader, the listener, the viewer, the audience, the decoder, or the communicator. Khalayak is one of the elements of the communication process. Therefore, the audience should not be ignored because it does not succeed in a communication process highly determined by the audience. (Cangara, 2010: 157). For a communicator, communication can be said to be successful when a message delivered through a channel or medium can be received, understood, and interpreted positively by the target audience, in the sense that it corresponds to the expectations of the communicator. (Sendjaja, 2005: 24). According to the common sense of communication, the person to whom a message is transmitted is called the recipient, the audience, or the communicator. Nevertheless, the public is only a temporary role. At the turn of sending the message, the recipient will start sending a next message and at that point the audience has changed the role of the communicator. The same concept applies to political communication. The side that was once known as the communicator or channel, at other times can also be identified as the Khalayak is one of the elements of the communication process. Therefore, the audience should not be ignored because it does not succeed in a communication process highly determined by the audience.